The world's most beautiful libraries = Die Schönsten Bibliotheken der Welt = Les plus belles bibliothèques du monde - Listri, Massimo 1953-; Ruppelt, Georg 1947-; Sladek, Elisabeth 1956- (Taschen, 2024)
From the mighty halls of ancient Alexandria to the coffered ceilings of the Morgan Library in New York, human beings have had a long, enraptured relationship with libraries. Like no other concept and like no other space, the collection of knowledge, learning, and imagination offers a sense of infinite possibility. It’s the unrivaled realm of discovery, where every faded manuscript or mighty clothbound tome might reveal a provocative new idea, a far-flung fantasy, an ancient belief, a religious conviction, or a whole new way of being in the world.In this new photographic journey, Massimo Listri travels to some of the oldest and finest libraries to reveal their architectural, historical, and imaginative wonder. Through great wooden doors, up spiraling staircases, and along exquisite, shelf-lined corridors, he leads us through outstanding private, public, educational, and monastic libraries, dating as far back as 766. Between them, these medieval, classical, baroque, rococo, and 19th-century institutions hold some of the most precious records of human thought and deed, inscribed and printed in manuscripts, volumes, papyrus scrolls, and incunabula. In each, Listri’s poised images capture the library’s unique atmosphere, as much as their most prized holdings and design details.Featured libraries include the papal collections of the Vatican Apostolic Library and the Trinity College Library, home to the Book of Kells and Book of Durrow. With meticulous descriptions accompanying each featured library, we learn not only of the libraries’ astonishing holdingsfrom which highlights are illustratedbut also of their often lively, turbulent, or controversial pasts. Like the Franciscan monastery in Lima, Peru, with its horde of archival Inquisition documents.At once a bibliophile beauty pageant, an ode to knowledge, and an evocation of the particular magic of print, this compact edition of our best-selling XXL-title is above all a cultural-historical pilgrimage to the heart of our halls of learning, to the stories they tell, as much as those they gather in printed matter along polished shelves